Identification of the PIP2-binding site on Kir6.2 by molecular modelling and functional analysis. - Haider, S; Tarasov, A; Craig, T; Sansom, M; Ashcroft, F (2007)
ATP-sensitive potassium (K(ATP)) channels couple cell metabolism to electrical activity by regulating K(+) fluxes across the plasma membrane. Channel closure is facilitated by ATP, which binds to the pore-forming subunit (Kir6.2). Conversely, channel opening is potentiated by phosphoinositol bisphosphate (PIP(2)), which binds to Kir6.2 and reduces channel inhibition by ATP. Here, we use homology modelling and ligand docking to identify the PIP(2)-binding site on Kir6.2. The model is consistent with a large amount of functional data and was further tested by mutagenesis. The fatty acyl tails of PIP(2) lie within the membrane and the head group extends downwards to interact with residues in the N terminus (K39, N41, R54), transmembrane domains (K67) and C terminus (R176, R177, E179, R301) of Kir6.2. Our model suggests how PIP(2) increases channel opening and decreases ATP binding and channel inhibition. It is likely to be applicable to the PIP(2)-binding site of other Kir channels, as the residues identified are conserved and influence PIP(2) sensitivity in other Kir channel family members.